A3_3 A Green Party - Meggi, Dikshita; Yeo, Adam; Routledge, Hannah; Lewis, Jacob (Physics Special Topics, 2021)
A model of a musical event venue is devised to convert the sound energy produced by a source in a dome-shaped air cavity surrounded by water into thermal energy to vaporise it and run a steam turbine. By consideration of acoustic impedance’s and attenuation within relevant mediums, the time-scale after which steam is produced is found to be extremely large. The potential of this model is thus limited unless optimised by design and choice of materials.